Pengaruh Penerapan Metode Simak Terka terhadap Kemampuan Menyimak Peserta Didik - Jurana, Jurana; Halimah, Andi; Hasrianti, Andi (FONDATIA, 2025)
Although listening skills constitute a crucial component of Indonesian language instruction at the primary school level, students' Enthusiasm and competence in this area remain notably weak. This study aims to examine the effect of the Simak Terka method on improving the listening skills of fourth-grade students at SDN 028 Ugi Baru, Polewali Mandar Regency. A quantitative approach was employed using a pretest-posttest control group experimental design, involving 20 students selected through total sampling. Data were collected through listening tests (pretest and posttest) and documentation, then statistically analyzed using normality testing and the paired sample t-test at a 0.05 significance level. The results indicate a significant improvement in listening skills following the implementation of the Simak Terka method, as evidenced by a two-tailed significance value of 0.000 (p < 0.05). The average pretest score of 45.00 (low category) increased to 74.50 (high category) in the posttest. These findings confirm the effectiveness of the Simak Terka method in enhancing listening skills at the elementary level. The study contributes empirical support to Indonesian language instruction strategies focused on receptive skills and recommends the adoption of similar methods in primary education contexts to enhance instructional effectiveness.